2013
DOI: 10.1038/bjc.2013.114
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tamoxifen±aminoglutethimide in normal weight and overweight postmenopausal patients with hormone receptor-positive breast cancer: an analysis of 1509 patients of the ABCSG-06 trial

Abstract: Background:There exists evidence that body mass index (BMI) impacts on the efficacy of aromatase inhibitors in patients with breast cancer. The relationship between BMI and the efficacy of tamoxifen is conflicting. We investigated the impact of BMI on the efficacy of single tamoxifen and tamoxifen plus an aromatase inhibitor in the well-defined prospective study population of the ABCSG-06 trial.Methods:ABCSG-06 investigated the efficacy of tamoxifen vs tamoxifen plus aminoglutethimide in postmenopausal women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…In this reanalysis, we did not observe any impact of BMI on the frequency of side effects, which is in line with previous reports (Pfeiler et al , 2011, 2013). Overweight patients had the same frequency of side effects as normal weight patients regarding long-term endocrine therapy with anastrozole.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this reanalysis, we did not observe any impact of BMI on the frequency of side effects, which is in line with previous reports (Pfeiler et al , 2011, 2013). Overweight patients had the same frequency of side effects as normal weight patients regarding long-term endocrine therapy with anastrozole.…”
Section: Discussionsupporting
confidence: 93%
“…For the analyses, we combined overweight and obese patients. As previously shown, the prognostic and predictive impact of BMI is more distinct in obese than in overweight (Sestak et al , 2010; Kwan et al , 2012; Pfeiler et al , 2013). We can therefore not completely exclude that the data presented here are mainly driven by the group of obese patients, and further differentiation between limited weight excess and severe obesity is beyond numerical reason in our trial.…”
Section: Discussionmentioning
confidence: 69%
“…[25] A secondary analysis on 1509 patients found that overweight women had poorer distant-recurrence-free survival compared to normal weight women (HR 1.54; 95%CI 1.00–2.35) and obese women had poorer disease-free survival (HR 1.45; 95%CI 1.03–2.02), distant recurrence-free survival (HR 1.79; 95%CI 1.11–2.87 and overall survival (HR 1.82; 95%CI 1.12–2.91) compared to normal weight women. [26] Obese women in the tamoxifen + AI group also had worse disease-free survival (HR 1.78; 95%CI 1.12–2.83), distant recurrence-free survival (HR 2.43; 95%CI 1.25–4.70) and overall survival (HR 2.28; 95%CI 1.16–4.51) compared to normal weight women receiving tamoxifen + AI. No differences across BMI were detected in the tamoxifen only group [26]…”
Section: Obesity May Alter the Efficacy Of Treatment For Hormone-recementioning
confidence: 99%
“…[26] Obese women in the tamoxifen + AI group also had worse disease-free survival (HR 1.78; 95%CI 1.12–2.83), distant recurrence-free survival (HR 2.43; 95%CI 1.25–4.70) and overall survival (HR 2.28; 95%CI 1.16–4.51) compared to normal weight women receiving tamoxifen + AI. No differences across BMI were detected in the tamoxifen only group [26]…”
Section: Obesity May Alter the Efficacy Of Treatment For Hormone-recementioning
confidence: 99%
“…1B.3). Studies comparing treatment efficacy of estrogen targeting between obese and normal weight patients showed contradicting results (Ewertz et al, 2011;Pfeiler et al, 2013). As can be expected, ER positive tumor cells can indirectly be influenced by oophorectomy.…”
Section: E2 -Clinical Datamentioning
confidence: 99%